Prospective Outcomes Study of the Impact of Nasal Surgery on Sleep Quality. (23rd August 2013) - Stapleton, Amanda L.; Gillman, Grant
Abstract : Objectives: Evaluate the impact of functional nasal airway surgery on the quality of sleep in patients using validated outcomes measurements. Study Design: Prospective, single center, outcome study of sleep quality before and after functional nasal surgery in patients with nasal airway obstruction treated from August 1, 2011, to August 1, 2013. Patients >18 years old with symptomatic structural nasal airway obstruction treated surgically at an academic otolaryngology practice. Intervention: Primary septoplasty, revision septoplasty, functional septorhinoplasty. Methods: Patients completed the Nasal Obstruction Symptom Evaluation (NOSE) scale (0‐100 scale), Epworth Sleepiness Scale (ESS) (0‐21 scale), the Pittsburgh Sleep Quality index (PSQI) (0‐21 scale), and Likert scales pre‐operatively and at 3 months post‐operatively. The impact of nasal surgery outcome on sleep quality was analyzed. Linear regression analyses were carried out to identify independent variables affecting sleep outcomes in nasal surgery patients. Results: 48 patients enrolled, and 7 were lost to follow‐up. 41 patients for preliminary analysis: 19 septoplasty, 4 revision, and 18 functional septorhinoplasty. Mean NOSE scores decreased from 67 pre‐op to 17 at 3 month follow‐up. ESS scores decreased from 7.8 to 5.8. PSQI decreased from 7.9 pre‐op to 5.0 post‐op. Additional analyses are ongoing. Conclusions: Nasal airway surgery does have an effect on sleep quality when evaluated using validated outcomes measurements. The NOSE score showed the most significant improvement in symptomatology. The ESS and PSQI also showed improved sleep quality after nasal surgery.